2016
DOI: 10.1080/19345747.2016.1236160
|View full text |Cite
|
Sign up to set email alerts
|

Impacts After One Year of “Healing Classroom” on Children's Reading and Math Skills in DRC: Results From a Cluster Randomized Trial

Abstract: This work is published through a Creative Commons licencethe default licence is CC BY-NC unless stated otherwise.This work has been licensed by the copyright holder for distribution in electronic format via any medium for the lifetime of the OpenDocs repository for the purpose of free access without charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…Third, these results suggest that understanding how to improve children's literacy scores appears to require attention to family processes and to classroom/school processes beyond the supportiveness and predictability of school ecologies. While previous analyses indicated that LRHC significantly improved children's literacy scores (Aber et al, in press), our analysis suggests that it did not necessarily do so by improving school-level supportiveness and predictability. Given that LRHC is a teacher professional development program, it is possible that the intervention improved children's literacy scores by improving teachers’ own reading ability or their ability to teach literacy skills, two constructs that are not captured in our measures of the classroom ecology.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…Third, these results suggest that understanding how to improve children's literacy scores appears to require attention to family processes and to classroom/school processes beyond the supportiveness and predictability of school ecologies. While previous analyses indicated that LRHC significantly improved children's literacy scores (Aber et al, in press), our analysis suggests that it did not necessarily do so by improving school-level supportiveness and predictability. Given that LRHC is a teacher professional development program, it is possible that the intervention improved children's literacy scores by improving teachers’ own reading ability or their ability to teach literacy skills, two constructs that are not captured in our measures of the classroom ecology.…”
Section: Discussioncontrasting
confidence: 83%
“…Correlational, longitudinal, and experimental evidence from high-income countries supports the pathways in our theory of change (for overviews on evidence supporting specific mediating and outcome constructs, see Aber et al, in press; and Torrente et al, 2015, in press). First, a recent meta-analysis of over 200 school-based social–emotional learning (SEL) programs in the United States and other high-income countries shows that such programs are a viable and effective approach to improving both academic and socioemotional outcomes (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011; see Figure 1, Paths c and d).…”
Section: Lrhc In the Drc: Theory Of Change And Impactssupporting
confidence: 56%
See 3 more Smart Citations